Essays on leasing Kansas agricultural land - Arnold, Chelsea Jewel (Kansas State University, 2021)
Nearly half of all the farmland in the United States is farmed by a producer that does not own the land. This is especially true in midwestern states such as Kansas. Leasing, versus owning, farmland requires producers to have significantly less capital upfront, thereby reducing overall financial risk exposure. When deciding to lease, or who to lease to/from, both landowners and tenants face several decisions in contract specifics that benefit both parties. Contract choice in farmland leasing includes many factors outside of simply which contract is preferred as each contract choice brings its own set of costs and benefits for both the landowner and tenant. In Essay 1 of this dissertation, the role of risk in contract choice is studied. A unique dataset of landowners and tenants in Kansas is used to examine the role of risk in their contract choices. Results indicate that greater production risk and more risk-averse landowners lead to use of fixed cash rent contracts. As there can be potentially many relationship variables that affect contract choices, a penalized regression is used to examine whether the inclusion of relationship variables affect the finding and find that the results are robust. Understanding the role of risk in farmland contract choices is important to assess the welfare consequences of farm policies or environmental changes that affect production risk. When deciding who to lease their land to, landowners can face several choices in tenants with a wide variety of attributes such as experience level, age, and relationship to the landowner. Experience level, or years of farming experience, is an important factor that landowners utilize in determining who to lease to and at what rate. This can leave young producers, who typically have lower experience levels, at a greater disadvantage when trying to find access to farmland. Using a dataset built from responses of surveys sent to landowners across the state of Kansas, Essay 2 focuses on landowners’ willingness-to-lease to young producers under different condition. A discrete choice model is used to find Kansas landowners’ willingness-to-lease to tenants at three different experience levels and three different relationship levels with the landowner. Empirical results indicate that a young producer with no experience is less preferred than a tenant with more years of experience and may, therefore, need to offer the landowner a higher cash leasing amount before the landowner is willing to lease to them. For young producers with higher experience levels, landowners will accept a marginally discounted rate when compared to not leasing to anyone at all. Relationships such as family/friend and acquaintances between landowners and young producers are also given a discounted leasing rate when compared to the landowner leasing to a stranger. This study not only fills a literature gap of landowner-young producer relationships and willingness-to-pay, but it also lays the foundation for policies to be implemented. Young producers with no experience are at the greatest disadvantage with low access to capital and heavily reliant on access to leased farmland, yet Kansas landowners require a higher leasing rate to rent to young producers. The results of this essay are key in policy implications, but also in educating landowners that their stated belief and attitudes towards young producers do not hold when faced with a monetary-based decision. This dissertation is comprised of two unique studies that focus on farmland leasing in Kansas and the relationships and factors that can affect them. Both studies present results that benefit Kansas landowners and producers by offering insight and education about how leasing contracts and arrangements can be made that benefit both landowner and producer.
Keywords: Farmland leasing; Landowner tenant relationships; Contract choice